EFFECTS OF NEEM OIL ON THE PRESERVATION OF MILICIA EXCELSA: EVALUATION OF TERMITICIDAL EFFECTIVENESS - Enukwa, Ettagbor Hans; Ndang, Yilom Hyginus (International Journal of Research -GRANTHAALAYAH, 2021)
Wood usage has increased with time, thus, there is need to investigate how wood can be treated with human and environmentally friendly preservative which is effective in protecting wood from termites and other agents of wood deterioration, or improve the wood physical, chemical, mechanical and biological characteristics. The aim of this study was therefore to evaluate the effects of neem oil on Milicia excelsa wood preservation. Treated and untreated pieces of Milicia excelsa wood samples were used to carry out this experiment, a soil bed, and an internal wood exposure to termite’s test was carried out, and measurements taken using a digital weighing machine. The results obtained showed that, when Milicia excelsa is treated with neem oil, its Rate of Decay (ROD) reduces as compared to the untreated pieces. Also, neem oil treated wood when exposed to termite’s attack experiences a slower weight loss compared to untreated samples with significant weight loss. Neem oil is thus not only effective in preserving woods, but also non- toxic to human and the environment.